2006
DOI: 10.1002/dev.20183
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of offensive responses during the maturation of play‐fighting into aggression in male golden hamsters

Abstract: In hamsters, the maturation of aggression during puberty is associated with a gradual reduction of offensive responses. The purpose of this study was to analyze the changes during this decrease to provide an enhanced description of the behavior. During early puberty, play-fighting is characterized by long and continuous contact duration throughout the encounter and repetitive attacks within bouts of agonistic interaction. By mid-puberty, adult patterns of offensive behavior emerge. Contact time becomes shorter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Juvenile and adolescent males tend to display more overt aggressive behaviors towards their opponents, while adult males communicate dominance through posturing and an array of both aggressive and submissive behaviors [15, 21, 47-49]. In the second experiment, we found long term changes in agonistic behaviors (aggressive and submissive behaviors) due to AAS exposure during adolescence and adulthood.…”
Section: Discussionmentioning
confidence: 81%
“…Juvenile and adolescent males tend to display more overt aggressive behaviors towards their opponents, while adult males communicate dominance through posturing and an array of both aggressive and submissive behaviors [15, 21, 47-49]. In the second experiment, we found long term changes in agonistic behaviors (aggressive and submissive behaviors) due to AAS exposure during adolescence and adulthood.…”
Section: Discussionmentioning
confidence: 81%
“…It has been suggested that low levels of rough and tumble play may indicate vulnerability toward reduced motivated behavior in adulthood (Trezza et al, 2010). For example, animal models have demonstrated a relationship between rough and tumble play and future sexual and aggressive behaviors (van den Berg et al, 1999a; Cervantes et al, 2007; Wommack and Delville, 2007). Thus, decreased rough and tumble play in MOR-F1 males may suggest an increased risk for deficits in other motivated behavior in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…On P43, play-deprived animals were re-housed with their play-exposed littermates. We targeted P21–P42 for play deprivation because this is the period of early puberty when rates of social play peak in hamsters (Cervantes, Taravosh-Lahn, Wommack, & Delville, 2007; Pellis & Pellis, 1988). …”
Section: Methodsmentioning
confidence: 99%